Integrated Optical Power Splitter With Continuously Adjustable Power Splitting Ratio - Shasha Liao; Hang Bao; Tiantian Zhang; Jiwei Liu; Xi Liao; Li Liu (IEEE Photonics Journal)
Optical power splitter (OPS) as one of the basic elements in photonic integrated circuits (PIC) is widely used in many fields. The OPS with continuously adjustable power splitting ratio (PSR) can improve the flexibility of PIC and also simplify the PIC system. We propose and demonstrate an integrated OPS based on silicon-on-insulator. Our scheme combines several common structures such as 2 × 2 multimode interference coupler, waveguide grating and slot. The PSR of the OPS can be continuously adjustable by tuning the wavelength of the input signal or the voltages applied to the electrodes on the chip. The maximum tunable range of the PSR is from 28.2 dB to −1.7 dB when no voltages are applied to the electrodes and the wavelength of the input signal varies from 1542.62 nm to 1547.94 nm. And the maximum and minimum tunable ranges of the PSR are 35 dB and 0.4 dB, respectively, when the power consumption of the micro-heaters varies from 0 to 27 mW. So, our OPS can be both temperature-sensitive and temperature-insensitive. Our scheme has the advantages of compact structure and high flexibility, and it can be widely used in optical switching, signal channel division and power distribution.